Imaging-guided percutaneous transthoracic needle biopsy of nodules in the lung base: fluoroscopy CT versus cone-beam CT. Issue 5 (May 2022) - Ren, Q.; Zhou, Y.; Yan, M.; Zheng, C.; Zhou, G.; Xia, X.
Abstract : AIM: To compare the diagnostic performance and safety of fluoroscopy computed tomography (FCT)-guided to cone-beam CT (CBCT)-guided percutaneous transthoracic needle biopsy (PTNB) in patients with nodules in the lung base. MATERIALS AND METHODS: The clinical data of 379 patients (228 in the FCT group and 151 in the CBCT group) with nodules in the lung base who underwent FCT-guided or CBCT-guided PTNB from September 2009 to March 2020 were analysed retrospectively. Study outcomes included patient demographics, nodule characteristics, technical success, pathological diagnosis, complications, and radiation exposure. RESULTS: PTNB technical success rates were 98.2% in the FCT group and 98.7% in the CBCT group ( p= 0.548). For larger lesions (>2 cm in diameter), PTNBs under FCT had similar diagnostic accuracy (95.5% versus 93.64%), incidence of pneumothorax (31.5% versus 21.3%) and radiation exposure (16.8 ± 6.1 versus 15.2 ± 4 mSv) compared to those under CBCT guidance. For smaller lesions (≤2 cm in diameter), the diagnostic accuracy was similar (92.86% versus 100%), but there was a higher incidence of pneumothorax (66.7% versus 31%, p= 0.030) and more radiation exposure (19.9 ± 8.4 versus 15.3 ± 5 mSv, p= 0.040) under FCT guidance than CBCT. CONCLUSION: PTNBs under FCT and CBCT guidance had similar performance for larger lesions in lung base. CBCT guidance performed better for smaller lesions in terms of radiation dose and complications. Radiologists could optimise the technological resources based on equipment availability and lesion characteristics. Highlights: PTNB under Fluoro-CT and CBCT guidance had similar performance in larger nodules. More pneumothorax occurs under fluoro-CT guidance in smaller nodules. Fluoro-CT-guided PTNB produced more radiation exposure in smaller nodules.